Development of Interactive Digital Learning Multimedia Applications as Independent Learning Module in 2-Dimensional Game Programming Courses - Yeni Nurhasanah; Khairunisa, Yuyun; Kuswoyo, Deni (JTP - Jurnal Teknologi Pendidikan, 2022)
Learning activities at the Creative Media State Polytechnic after the pandemic period, especially in the design department of the game technology study program, were held in blended learning. Blended learning is the right choice of learning because it needs adaptation from lecturers and students, where previously learning was held fully online, now it is held online and offline. Blended learning activities can be very effective and efficient in their implementation if the learning process is well prepared. One of the learning activities carried out is independent learning activities. Therefore, this study aims to produce a learning application that can be used as an independent learning module so that students can learn without being assisted by anyone just by using this independent learning module. The approach taken is the ADDIE development method. The ADDIE development model consists of five stages, namely analysis, design, development, implementation, and evaluation. Expert response to this learning application is a crucial thing to do. This application is evaluated by an expert with a background in graphic design, learning media, and communication. The independent learning module application was successfully developed and implemented in semester 3 of the 2-dimensional game programming course.